The Midwives’ Roles in Community-Based Stunting Prevention: A Qualitative Study in Primary Health Services - Aryudaningrum, Nastiti; Hidayat, Asri; Kurniawati, Herlin Fitriani (Gaster, 2025)
Background Stunting remains a major public health concern in many low- and middle-income countries, with long-term consequences for cognitive development, educational achievement, and economic productivity. Midwives, particularly in decentralized health systems like posyandu in Indonesia, play a vital role in early prevention efforts. However, limited research has explored their contextualized contributions within community-based health services. Objective This study aimed to explore the strategic roles of midwives in preventing stunting, focusing on their functions as healthcare providers, educators, and community facilitators. Methods A qualitative phenomenological study was conducted involving six community midwives selected via purposive sampling. Data were collected through semi-structured in-depth interviews and analyzed thematically. Triangulation was performed using additional informants including coordinating midwives, nutritionists, and community health workers. Results Four primary themes emerged: (1) midwifery care in stunting prevention; (2) community engagement and educational activities; (3) communication and health promotion strategies; and (4) identification of local health issues. Midwives were actively involved in growth monitoring, nutrition counseling, home visits, and cross-sectoral collaboration. Challenges included low community participation, persistent stigma, and limited awareness about stunting. Conclusion Community midwives play a strategic role in stunting prevention through education, early detection, and collaborative community engagement. Strengthening their communication skills, cultural competence, and integration with local stakeholders is essential for optimizing the impact of stunting prevention programs and ensuring sustainable public health outcomes.